Differentiated social studies based on hypermedia e-modules to foster sustainable social attitudes of elementary students - Yuyun Dwi Haryanti Haryanti; Mohamad Syarif Sumantri; Hamdan Tri Atmaja; Sapriya; I Gusti Agung Ayu Wulandari; Seah Siok Peh; Rina Nengsih; Rahma Halipah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
The present study examines the effect of differentiated social studies supported by hypermedia e-modules on the development of sustainable social attitudes among elementary students. A quasi-experimental design with a pre-test–post-test control group is employed. The participants were 60 fifth-grade students from an elementary school in Majalengka, Indonesia. They were selected using total sampling and divided into an experimental group (n = 30) and a control group (n = 30). The experimental group receives differentiated social studies instruction supported by hypermedia e-modules, while the control group receives instruction using conventional textbooks. Data were collected using a 10-item sustainable social attitudes questionnaire that measures empathy, social responsibility, cooperation, tolerance, environmental concern, and social awareness. The instrument demonstrates acceptable validity and reliability (Cronbach’s α = 0.744). Data were analyzed using descriptive statistics and an independent samples t-test. The results indicate that the experimental group obtained higher post-test scores (M = 85.60, SD = 8.66) than the control group (M = 80.90, SD = 9.11), with a statistically significant difference, t(58) = 2.05, p = 0.045, and a moderate effect size (Cohen’s d = 0.53). These findings imply that integrating hypermedia e-modules within differentiated social studies instruction can support the development of sustainable social attitudes among elementary students. The study contributes to the growing body of research on technology-supported differentiated learning in elementary social studies, although further research with larger samples and longer interventions is recommended.